2021
DOI: 10.1111/os.12979
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Therapeutic Strategies for Joint‐Preserving Surgery for Non‐Traumatic Osteonecrosis of the Femoral Head between the United States and Japan: A Review of the Literature

Abstract: For patients with non‐traumatic osteonecrosis of the femoral head (ONFH), core decompression (CD) and bone grafts (BG) are mainly performed in the West, while osteotomy is found to be predominant in Japan. It is not well recognized how the surgical procedures for joint preservation in patients with ONFH are completely different between the United States and Japan. This paper identifies the contexts and the differences in treatment strategies for ONFH between the two countries. We compared the surgical trends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Preserving the patient's own hip joint and prolonging the service life of the joint has always been the goal pursued by clinicians. In the West, the most commonly used methods for adult hip preservation are core decompression (CD) and bone grafting [ 31 ], but the collapse rate of such minimally invasive hip preservation surgery is as high as 50% at two years after operation [ 32 ]. In addition, for patients with large necrosis or ARCO stage III/IV, nonsurgical hip preservation or CD often cannot prevent progressive collapse of the femoral head [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preserving the patient's own hip joint and prolonging the service life of the joint has always been the goal pursued by clinicians. In the West, the most commonly used methods for adult hip preservation are core decompression (CD) and bone grafting [ 31 ], but the collapse rate of such minimally invasive hip preservation surgery is as high as 50% at two years after operation [ 32 ]. In addition, for patients with large necrosis or ARCO stage III/IV, nonsurgical hip preservation or CD often cannot prevent progressive collapse of the femoral head [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for patients with large necrosis or ARCO stage III/IV, nonsurgical hip preservation or CD often cannot prevent progressive collapse of the femoral head [ 33 35 ]. THA is considered to be the ultimate method for advanced ONFH and secondary end-stage osteoarthritis [ 31 ]. For children with avascular necrosis of the femoral head, studies have shown that conservative treatment can achieve good results in a large proportion of patients [ 36 – 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases opting for THA is increasing, which can be attributed to the improvements in long-term efficacy. Furthermore, younger patients with ONFH are unwilling to undergo joint-sparing surgery that requires long-term hospitalization ( 143 ). Thus, joint replacement surgery is currently the most preferred treatment method for advanced NONFH.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…According to statistics from the World Health Organization, the age of patients with ONFH is mostly between 30 and 50 years old. Also, the incidence rate of ONFH is gradually increasing with age [ 4 ]. This disease is more harmful.…”
Section: Introductionmentioning
confidence: 99%